Influence of Service Quality towards Patient’s Satisfaction of Outpatient Department in Private Hospitals in Jakarta - Maria Vashti Zerlinda Lesmana; Hendra Achmadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Medical industry is essential in building a prosperous country. With the rise of knowledge in public masses in Indonesia, many citizen demand for a higher quality of service when it comes to medical assistance. This study was conducted to further examine influence of service quality towards patient’s satisfaction of outpatient department in private hospitals in Jakarta. Quantitative method is used in this study by using 160 subjects gathered as primary data distributed through google forms. Data collected will then be analyzed using PLS-SEM to evaluate correlation between the two factors of research. In this study we found that responsiveness and empathy significantly gives positive impact towards patient’s satisfaction with T statistic of 3.203 and 2.996 respectively. Overall, it can be concluded that service quality, especially responsiveness and empathy has positive impact towards patient’s satisfaction of outpatient department in private hospitals in Jakarta. It is important for hospitals to understand this in order to give better services to patients.